Platelet activation independent of pulmonary inflammation contributes to diesel exhaust particulate-induced promotion of arterial thrombosis. Issue 1 (December 2015) - Tabor, Caroline; Shaw, Catherine; Robertson, Sarah; Miller, Mark; Duffin, Rodger; Donaldson, Ken; Newby, David; Hadoke, Patrick
Abstract Background Accelerated thrombus formation induced by exposure to combustion-derived air pollution has been linked to alterations in endogenous fibrinolysis and platelet activation in response to pulmonary and systemic inflammation. We hypothesised that mechanisms independent of inflammation contribute to accelerated thrombus formation following exposure to diesel exhaust particles (DEP). Methods Thrombosis in rats was assessed 2, 6 and 24 h after administration of DEP, carbon black (CB; control carbon nanoparticle), DQ12 quartz microparticles (to induce pulmonary inflammation) or saline (vehicle) by either intra-tracheal instillation (0.5 mg, except Quartz; 0.125 mg) or intravenous injection (0.5 mg/kg). Thrombogenicity was assessed by carotid artery occlusion, fibrinolytic variables and platelet-monocyte aggregates. Measures of inflammation were determined in plasma and bronchoalveolar lavage fluid. Tissue plasminogen activator (t-PA) and plasminogen activator inhibitor (PAI)-1 were measured following direct in vitro exposure of human umbilical vein endothelial cells (HUVECs) to DEP (10–150 μg/mL). Results Instillation of DEP reduced the time to thrombotic occlusion in vivo, coinciding with the peak of DEP-induced pulmonary inflammation (6 h). CB and DQ12 produced greater inflammation than DEP but did not alter time to thrombotic occlusion. Intravenous DEP produced an earlier (2 h) acceleration of thrombosis (as did CB) without pulmonary or systemic inflammation. DEP inhibited t-PA and PAI-1 release from HUVECs, and reduced the t-PA/PAI-1 ratio in vivo; similar effects in vivo were seen with CB and DQ12. DEP, but not CB or DQ12, increased platelet-monocyte aggregates. Conclusion DEP accelerates arterial thrombus formation through increased platelet activation. This effect is dissociated from pulmonary and systemic inflammation and from impaired fibrinolytic function.